Regulatory Challenges in the COVID-19 Era: The Case of Tunisia. (4th June 2022) - Cherif, Dora; Felfel, Hajer; Drira, Chema; Aounallah, Mariam; Kadri, Meriem; Ben Rayana, Mohamed Chiheb; Razgallah Khrouf, Myriam
Abstract: In view of the possible disruptions in the manufacturing and supply of health products following the coronavirus disease 2019 (COVID-19) pandemic, the Tunisian medicines regulatory authority was mobilized to guarantee patient safety. Teleworking has become the ultimate way of service continuity. The planning was revised according to health priorities. Work procedures were set online. A minimum list of medicines known as "medicines of health and strategic interest" was established. The Directorate of Pharmacy and Medicines (DPM) has been working on updating medicines stock data. A provisional suspension of authorizations for medicines export for 1 mo was decided. A fast-track procedure allowing the validation of alternative sources of raw materials has been put in place. An appeal for a fast track manufacture of hydroalcoholic gel/solutions was launched. A Monitored Emergency Use of Unregistered and Investigational Interventions (MEURI) procedure has been adopted in order to dispense off-label prescriptions of hydroxychloroquine and azithromycin combination. Focus groups were organized in order to set up therapeutic trials exploring possible strategies of COVID-19 treatment, such as serotherapy and BCG vaccine. This proactive and anticipatory policy has made it possible to meet the health challenges dictated by this crisis.